Using Videoconferencing to Establish and Maintain a Social Presence in Online Learning Environments - Robert A. Moody; Regi L. Wieland (Educational Considerations, 2010)
For 30 years, the educational administration program faculty at Fort Hays State University (FHSU) followed a traditional face-to-face (F2F) on campus approach to course delivery.
Keywords: desktop videoconferencing (DVC); instruction. Programs; course delivery; strategies; educational; administration; successful; learning; environment